Barriers and Facilitators to School‐Based Health Centers: pilot Data From 3 Sites in Georgia. (18th December 2019) - Zarate, Raul Perez; Johnson, Leigh; Mogendi, Simon; Hogue, Carol; Johnson, Veda; Gazmararian, Julie
ABSTRACT: BACKGROUND: School‐based health centers (SBHCs) provide opportunities for offering quality service to underserved populations. The objectives of this study were to: (1) document the SBHC process at different locations and evaluate their similarities and differences; (2) explore SBHC clinic staff satisfaction; and (3) identify facilitators and barriers to utilizing SBHCs. METHODS: Three Georgia SBHCs located in either predominantly Caucasian, African American, or Hispanic elementary schools were included in this study. Mixed methods data collection efforts included: (1) observational assessment of each SBHC; (2) interviews with 7 clinic administrators and staff; and (3) focus group discussions (N = 5) with parents of children that do and do not utilize SBHCs. RESULTS: Observational assessments indicated some clinics have more resources available than others. In‐depth interviews found that centers are functioning at capacity, with potential for expansion and greater workload. Focus groups revealed that parents are satisfied with services provided, the price of the care, and the convenience of the centers. However, barriers have made utilization difficult for lower income families. CONCLUSIONS: Although most SBHC goals are being met, staff realize that further development and funding must be obtained to meet the needs of their communities.